EVALUATION OF COMPETITIVENESS OF PAINT AND FINISH COATINGS DEPENDING ON THE TYPE OF COLORING OF THE BASE BLOCK - Yaremchuk, Larysa; Yakuba, Myroslava; Produsevych, Vasyl; Hogaboam, Liliya (Forestry, Forest, Paper and Woodworking Industry, 2024)
The main purpose of this study is to examine the value of the relative possession utility of a product finish with the different methods of base block coloring. Marketing research shows that buyers have high and low margins that create a framework, in which their perception of a product quality directly correlates to the price. The price that is lower than the lowest margin is perceived as underpriced, and the price, that is higher than the highest margin is perceived as overpriced. The value of competitiveness of a coating, developed on the base blocks with various kinds of coloring is a subjective method of a visual evaluation and conditionally-objective method to determine performance characteristics of the film. A point-based system, built on expert estimates of significance of certain product quality parameters for consumers is used to evaluate the competitiveness of the coatings. A future consumer will strive to buy an ecologically safe product; therefore, the main task of the producers is to supply a sustainable and durable product.